CO and CO_2 Concentration Measurements inside of Sealed CO_2 Laser Tubes: An Application Example for a Fiber-Optic Diode Laser Gas Sensor - Engelbrecht, Rainer; Schulz, R.; Striegler, Arne (16th Int. Conference on Lasers and Electrooptics CLEO Europe, München 23.- 27. Juni, 2003)
In this paper, we demonstrate the use of fiber-optic tunable diode laser spectrometer within the thermal tuning range from 1581 nm to 1584 nm a CO/CO/sup 2/ absorption line pair with a frequency separation of 3.65 GHz between the line centers for the measurements of CO and CO/sub 2/ concentrations inside the sealed CO/sub 2/ laser tubes. © 2003 IEEE.
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LEH.coandc